Factors associated with deep vein thrombosis recurrence at a cardiology department in sub-Saharan Africa - Lengani, EH; Nacanabo, WM; Tall/Thiam, A; Thiombiano, LP; Seghda, TAA; Tamou-Tabe, IY; Loya/Abouga, M; Dah, DC; Sawadogo, I; Dimzouré, SM; et al. (SA Heart Journal, 2026)
Objective: Deep vein thrombosis (DVT), once rare, has become increasingly common in Africa. This study aimed to identify factors associated with DVT recurrence. Methodology: We conducted a descriptive and analytical cross-sectional study from 1 January 2020 to 31 December 2024 at the cardiology department of Bogodogo University Hospital (CHU-B). Patients admitted to the department for DVT on venous echo-Doppler were included. Epidemiological, clinical, and paraclinical parameters were crossed in univariate and multivariate analyses. Results: During the study period, 164 cases of DVT were recorded out of 2 637 hospitalised patients, with a 6.22% hospital prevalence rate. The mean age was 51.4 years. Women were predominant (90, 55%), with a sex ratio of 0.8. Recurrences occurred in 27.44% of cases (n = 45). A sedentary lifestyle, prior DVT, and obesity were the most frequent thromboembolic risk factors. Multivariate analysis showed that a personal history of DVT (odds ratio [OR] 3; p = 0.03), obesity (OR 3.8; p = 0.005), and the femoral thrombus location (OR 2; p = 0.004) were significantly associated with DVT recurrence. Conclusion: DVT recurrences are becoming increasingly frequent, and their management requires accurate identification of the risk factors.